The Interaction Effect of Adverse Childhood Experiences and Socioeconomic Circumstances in Adolescent Depressive Symptomatology - Abrahamyan, A (2024)
"Purpose Limited research has examined the combined effects of psychosocial and material adversities experienced in childhood during adolescence, a sensitive period of rapid social, emotional, and cognitive development. We investigated the interaction effect of adverse childhood experiences (ACEs) and socioeconomic circumstances (SECs) during childhood on emerging self-reported depressive symptomatology among 13-year-old Portuguese adolescents. Methods We utilized data from 4,280 participants in the Generation XXI birth cohort, collected during the baseline (2005–2006), third (2016–2017), and fourth waves (2018–2020). Adjusted odds ratios and 95% confidence intervals (CIs) were obtained from binary logistic regression analyses to estimate the likelihood of depressive symptoms based on exposure to ACEs and adverse family SECs. The interaction effect of ACEs and SECs was evaluated in terms of departure from additive and multiplicative models. Results Adolescents who reported experiences of abuse, school-related problems, and household dysfunction, as well as those from less advantaged family SECs at age 10, were more likely to report moderate to severe depressive symptoms at age 13, compared to their more affluent counterparts. We observed a significant additive interaction between low household income and abuse in the development of moderate to severe depressive symptoms [relative excess risk due to interaction, 0.69, 95% CI: 0.11, 1.26]. This interaction remained statistically significant on a multiplicative scale [OR = 1.61, 95% CI: 0.99, 2.69]. Discussion ACEs and low family SECs during the first decade of life are associated with an elevated risk of moderate to severe depressive symptoms in adolescence."